1996
DOI: 10.1093/oxfordjournals.deafed.a014285
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Spoken Language in Deaf Children: Explaining the Unexplained Variance

Abstract: Using a large existing data base on children with severe and profound deafness, 10 children were identified whose level of spoken laguage was most above and 10 whose level was most below that expected on the basis of their hearing loss, age, and intelligence. A study of their personal characteristics, family background, and educational history identified factors associated with unusually high performance; these includes earlier use of binaural ear-level aids, more highly educated mothers, auditory/verbal or au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This attitude will no doubt empower the parents and facilitate support structures for the families (Bortoli & Bynes, 2002;Young & Tattersall, 2007). Musselman and Kircaali-Iftar (1996) hypothesised that children with advanced spoken skills have parents who view deafness in their child as a challenge and accept it, whereas children with low spoken skills have parents who view deafness as a difference to be accommodated. DesGeorges (2003) noted that the end point of the so-called 'adjustment' to having a deaf child is not acceptance, but positive action in the form of advocacy for both the child and family.…”
Section: Discussionmentioning
confidence: 99%
“…This attitude will no doubt empower the parents and facilitate support structures for the families (Bortoli & Bynes, 2002;Young & Tattersall, 2007). Musselman and Kircaali-Iftar (1996) hypothesised that children with advanced spoken skills have parents who view deafness in their child as a challenge and accept it, whereas children with low spoken skills have parents who view deafness as a difference to be accommodated. DesGeorges (2003) noted that the end point of the so-called 'adjustment' to having a deaf child is not acceptance, but positive action in the form of advocacy for both the child and family.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence across a variety of studies indicates that significant disruptions may occur in parent–child interactions among hearing mothers of infants and toddlers with SNHL (Meadow-Orlans et al 1997; Musselman and Kircaali-Iftar 1996; Quittner et al 1990; Quittner et al 2010). Observational studies have shown that, relative to mothers in either hearing or deaf dyads, hearing mothers of deaf children tend to be more controlling in their verbal and nonverbal interactions (Musselman and Churchill 1991), spend less time in coordinated joint attention with the child (Waxman et al 1996), and have greater difficulty responding to the child’s emotional and behavioral cues (Swisher 2010).…”
Section: Multivariable Analyses Of Language Learning After Early Cochmentioning
confidence: 99%
“…All children with hearing loss who participated in the current study were receiving intervention focused on the spoken communication modality: 4 were receiving auditory-verbal therapy and 1 was receiving auditory-oral therapy. Both types of intervention place considerable emphasis on attending to the auditory signal, which encourages active listening through a variety of strategies like acoustic highlighting and the use of parentese (Geers, Nicholas, & Sedey, 2003;Musselman & Kirkcaali-Iftar, 1996). As success on the JSR and EVDT requires that listeners pay close attention to specific aspects of the auditory signal, an intervention focused on audition may benefit children with hearing aids faced with these tasks.…”
Section: Discussionmentioning
confidence: 99%